The Impact of Instinct Motivation on Job Satisfaction: Analytical Study - Chiman Ahmed Hamad Ameen; Taha Omar Lateef (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
The purpose of this research is to investigate the impact of instinct motivation on job satisfaction in private banks in Erbil. A quantitative research method via a questionnaire was applied to measure the current study. The researcher selected 18 private banks in Erbil city, however each bank had approximately 35 employees therefore the target researcher population was 630 employees. Researchers sent out 125 surveys but only received 112 back, of which only 98 were really filled out. The study used SPSS to analyze and measure the developed research hypothesis which stated that instinct motivation has a significant influence on job satisfaction. The findings revealed that there is a positive and significant influence of instinct on job satisfaction. The study recommended for the future study to obtain larger sample size to measure similar studies.